Get well soon, Sippo, Level 3 (New Delhi: Om Books International, 2015)
When Sippo the hippo falls ill, his friends come up with a wonderful idea to cheer him up. Do his friends succeed? Does it make Sippo feel better? Read on to find out.
Children